Inovasi Percepatan Perizinan Pembangunan Perumahan Masyarakat Berpenghasilan Rendah (MBR) di Daerah - Zanariah Zanariah (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2019)
Part of the main matter of people's welfare is the fulfillment of housing needs Housing development is one of the important things in the regional development strategy, which involves broad aspects in the field of population, and is closely related to economic development and social life in the framework of strengthening national security. Considering the provision of housing is a basic right of the community, the government becomes the leader and prioritizes the priority of fulfilling its needs for the community, especially citizens with low income. The increase in house prices which is higher than the average inflation rate in Indonesia is one of the causes of the high housing backlog. This condition severely shock low income society or young families whose family economic growth was below the inflation rate. The Regional Government has a big role in the success of the policy, especially so that a million home national programs can reach the target by the end of the Medium-Term Development Plan 2019. The Economic Policy Package XIII (Paket Kebijakan Ekonomi XIII) that was issued by the Government some time ago regarding Housing for Low Income Society (MBR) is in line with the National Program for the Development of 1 (One) Million Houses. Through the Economic Policy Package, the government bring out a Government Regulation that simplified the number and timing of permits by removing or reducing various permits and recommendations for building MBR houses from as many as 33 permits and stages, to 11 permits and recommendations. With the reduction of the stages, the time for the construction of the MBR that has averaged 769-981 days can be accelerated to 44 days.